Analysis of Polymorphism of Uniparental Markers in Reindeer-Herding Populations: The Tozhu Tuvans of Russia and The Tsaatans Of Mongolia - Balinova, Natalia; Khomyakova, Irina; Ayyzhi, Elena; Dzhaubermezov, Murat; Litvinov, Sergey; Khusnutdinova, Elza; El’chinova, Galina; Zinchenko, Rena; Spitsyna, Nailya; Parik, Jüri; Reidla, Maere; Rootsi, Siiri (Collegium antropologicum, 2022)
We analyzed the data on the variability of the Y chromosome and mitochondrial DNA (mtDNA) in populations of the Tsaatans of Mongolia and the Tozhu Tuvans of Russia. The populations studied are characterized by low genetic diver¬sity for both marker systems. The analysis of Y chromosome haplogroups in the Tsaatan and Tozhu revealed three hap¬logroups in the Tsaatan and seven haplogroups in the Tozhu. The composition of the haplogroups is coherent to literature data on the Tuvans, which is explained by common origin. According to the data on mitochondrial DNA variability, 12 haplogroups were determined in 46 Tozhus, of which C4b (30.43%) and F1b1b (23.91%) are major haplogroups. According to the HVS–1 (HyperVariable Segment) data, 15 haplotypes were found in the Tozhu Tuvans and the diversity coefficient of 0.8677 turned out to be much lower than among the Torghut of Mongolia (0.9857). In 23 Tsaatans, 14 haplogroups were determined; the most common of which are C4b (22.73%) and C5a1 (18.18%). According to HVS-1, 14 haplotypes were revealed in the Tsaatan, the diversity is 0.9486. The data obtained on uniparental marker systems in the Tozhus and Tsaatans are due to the isolated and inaccessible taiga region and the manifestation of the “founder effect”. The Tsaatans are less polymorphic in terms of the variety of Y chromosome haplogroups, while the Tozhus are less polymorphic in terms of mitochondrial DNA, which is probably a consequence of a high rate of endogamic marriages in the populations studied.